Digitally immersive, international entrepreneurial experiences. Issue 6 (December 2020) - Dillon, Sarah M.; Glavas, Charmaine; Mathews, Shane
Highlights: Interaction patterns with digital technologies shape international experience. Distinct interaction patterns promote different experience types for entrepreneurs. Digital internationalisation experience is an important new type of experience. Digital internationalisation experience promotes opportunity exploitation. Immersive international experiences are important for generating new business ideas. Abstract: This study explores how entrepreneurs acquire international experiences within physical and digital business environments, and how these experiences influence the way international opportunities are recognised and exploited. Based on multiple case study evidence, including in-depth interviews with international entrepreneurs from 16 small virtual service firms, findings suggest entrepreneurs who interact with digital technologies in a responsive way in international settings may promote the emergence of a new type of experience: "digital internationalisation experience". This new type of experience, in turn, contributes to enhanced idea generation and opportunity confidence that enable international entrepreneurial exploitation.